Bidder preferences among auction institutions - Radosveta Ivanova-Stenzel; Tim Salmon (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
This study examines bidder preferences between alternative auction institutions. In particular we seek to experimentally characterize the degree to which bidders prefer an ascending auction over a sealed bid auction. We find very strong ceteris paribus preferences for the ascending institution with bidders choosing it overwhelmingly often when entry prices for the two auctions are the same. When the entry prices of the two auctions differ, many subjects can be shown to be willing to pay far more to enter the ascending auction than is explainable by their risk attitudes when accounting for their expectations about the risk preferences of their opponents.
urn:nbn:de:kobv:11-10049650
Keywords: C91; D44; 330; bidder preferences; private values; sealed bid auctions; ascending auctions